Overview of Immature Reticulocyte Fraction (IRF) and Red Cell Distribution Width-Coefficient Variation (RDW-CV) in Patients with Hemoglobin Levels Below 8 - Nurhayati, Nurhayati; Mastiadji, Bekti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Anemia is a condition in which the number or volume of erythrocytes or red blood cells and hemoglobin (Hb) molecules in the body are reduced. This condition occurs when hemoglobin levels or hematocrit (Ht) values decrease. Anemia can occur due to several factors, such as iron deficiency, vitamin B12 deficiency, folic acid deficiency, genetic factors, chronic diseases, intestinal worms, and bleeding. This study aims to determine the profile of immature reticulocyte fraction (IRF) and red cell distribution width-coefficient variation (RDW-CV) in patients with hemoglobin levels below 8. Method: This type of research is descriptive research, using purposive sampling with 30 respondents. Result: The results of this study obtained IRF RDW values -CV of 15 with a percentage of (50%), normal IRF RDW-CV of 10 with a percentage of (33%), normal IRF RDW-CV of 2 with a percentage of (7%), high IRF RDW-CV of 2 with a percentage of (7%), and low IRF RDW-CV of 1 with a percentage of (3%). Conclusion: The results showed that high IRF and high RDW-CV 15 with a percentage of 50% indicated a more active bone marrow response in producing new red blood cells in response to anemia and the presence of cell size differences known as anisocytosis.